Antidiabetic effects of protein hydrolysates from Trachinotus ovatus and identification and screening of peptides with α-amylase and DPP-IV inhibitory activities - Peng Wan; Bingna Cai; Hua Chen; Deke Chen; Xiangtan Zhao; Huabiao Yuan; Jingtong Huang; Xin Chen; Lianxiang Luo; Jianyu Pan (Current Research in Food Science, 2023)
In the present study, the antidiabetic properties of Trachinotus ovatus protein hydrolysates (TOH) in streptozotocin-induced diabetic mice were investigated, and peptides with α-amylase (AAM) and dipeptidyl peptidase IV (DPP-IV) inhibitory activities were identified and screened. The results showed that TOH alleviated body weight loss, polyphagia, blood glucose elevation and insulin secretion decline in diabetic mice. After 4 weeks of TOH administration, random blood glucose (RBG) decreased significantly. The TOH groups showed a dose-dependent reduction in fasting blood glucose (FBG), especially in the high-dose TOH group, which reduced FBG by 58% versus the effect of metformin. Moreover, TOH exerted a remarkable protective effect on hepatorenal function, as evidenced by increased superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPX) and decreased serum urea levels. Histopathological studies confirmed that TOH can significantly protect the kidney and pancreas from histological changes, which was of great benefit for ensuring the normal secretion of insulin and preventing the occurrence of complications such as diabetic nephropathy. Two fractions with higher inhibitory activity against AAM and DPP-IV, F4 and F6, were obtained from the ultrafiltration of TOH-2 (≤3 kDa). A total of 19 potentially active peptides from F4 and 3 potentially active peptides from F6 were screened by LC‒MS/MS combined with bioinformatic analysis. These peptides are small molecular peptides composed of 2–6 amino acids, rich in characteristic amino acids such as proline, arginine, phenylalanine and asparagine, and contain high proportions of peptides (68% for F4, 67% for F6) with hydrophobicity ≥50%. They offer potent antidiabetic potential and could potentially bind to the active sites in the internal cavities of the target enzymes AAM and DPP-IV. In summary, this study revealed for the first time the antidiabetic effects of protein hydrolysates of Trachinotus ovatus and their derived peptides, which are promising natural ingredients with the potential to be used for the treatment or prevention of diabetes.